Social Economic Factors Affecting Direct Sales Of Potatoes To Collectors In Koto Renah Village, Jangkat District, Merangin District - Fikriman Fikriman; Asminar Asminar; Evo Afrianto; Pitriani Pitriani; Ronsi Hartono (Baselang, 2023)
Potatoes are horticultural crops cultivated by farmers in Jangkat District. This study aims to determine whether socio-economic factors (farmer age, farmer education level, farming experience, land area, labor, capital, and price) affect direct sales to collectors by potato farmers in Koto Renah Village, Jangkat District, Merangin Regency. The research was conducted from January 13, 2020 to February 12, 2020, the data analysis method used in this research is quantitative descriptive analysis. The sample in this study were 78 potato farmers who sold directly to collectors. The data analysis method used is multiple linear regression, and hypothesis testing with the F test and t test. The result of the research shows that partially socio-economic factors are only variables of land area, labor force and price which have an effect as seen from the tcount ttable, while the variables age, education,experience and capital have no effect because tcount ttable. Simultaneously, the socio-economic factors have an effect as seen from the value Fcalculated (39,328) is greater than Ftable (3,120). socio-economic factors together have an effect of 51.2%.